Measurement of concentrations of four chemical ultraviolet filters in human breast tissue at serial locations across the breast. Issue 8 (16th April 2018) - Barr, L.; Alamer, M.; Darbre, P. D.
Abstract: The human population is widely exposed to benzophenone‐3 (BP‐3), octylmethoxycinnamate (OMC), 4‐methylbenzilidenecamphor (4‐MBC) and homosalate from their use in consumer goods to absorb ultraviolet (UV) light. Their oestrogenic activity and presence in human milk suggest a potential to influence breast cancer development. In this study, high‐performance liquid chromatography‐tandem mass spectrometry was used to measure concentrations of these UV filters in human breast tissue from three serial locations across the breast from 40 women undergoing mastectomy for primary breast cancer. One or more of these UV filters were quantifiable in 101 of 120 (84%) of the tissue samples and at least one breast region for 38 of 40 women. BP‐3 was measured in 83 of 120 (69%) tissue samples and at least one breast region for 33 of 40 women (range 0–26.0 ng g –1 tissue). OMC was measured in 89 of 120 (74%) tissue samples and at least one breast region for 33 of 40 women (range 0–58.7 ng g –1 tissue). 4‐MBC was measured in 15 of 120 (13%) tissue samples and at least one breast region for seven of 40 women (range 0–25.6 ng g –1 tissue). Homosalate was not detected in any sample. Spearman's analyses showed significant positive correlations between concentrations of BP‐3 and OMC in each of the three breast regions. For ethical reasons cancerous tissue was not available, but as the location of the cancer was known, Mann–Whitney U ‐tests investigated any link between chemical concentration and whether a tumour was present in that region or not. For the lateral region, more BP‐3 was measured when a tumour was present ( P = .007) and for OMC the P value was .061. For seven (of 40) women with measurable 4‐MBC, six of seven had measurable 4‐MBC at the site of the tumour. Abstract : High‐performance liquid chromatography‐tandem mass spectrometry was used to measure the concentrations of the ultraviolet filters benzophenone‐3, octylmethoxycinnamate, 4‐methylbenzilidenecamphor and homosalate in human breast tissue from three serial locations across the breast from 40 women undergoing mastectomy for primary breast cancer. Benzophenone‐3 was measured in 83 of 120 (69%) tissue samples (range 0–26.0 ng g –1 tissue). Octylmethoxycinnamate was measured in 89 of 120 (74%) tissue samples (range 0–58.7 ng g –1 tissue). 4‐Methylbenzilidenecamphor was measured in 15 of 120 (13%) tissue samples (range 0–25.6 ng g –1 tissue). Homosalate was not detected in any sample.